Penciptaan Nabi Adam dan Tugasnya di Bumi (Studi Komparasi Alkitab dan Al-Qur’an) - Mushofa, Chanif (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This paper aims to conduct a comparative study of the concept of the creation of the first human (Adam) in two scriptures of Abrahamic religions: the Bible and the Qur'an. The focus of this study is to explore the similarities and differences in the creation of Adam as the first human, as well as the responsibilities and roles assigned to humanity in the world. The research methodology involves textual analysis of the Bible and the Qur'an, along with references from various existing commentaries. The author finds that there are similarities in the elements constituting Adam in both the Qur'an and the Bible. The differences lie in the level of detail regarding the sequence of the creation process. The Bible provides information about the elements involved but does not elaborate on the formation process, whereas the Qur'an presents a more detailed account. Regarding the responsibilities and roles of humanity, the Qur'an outlines two main tasks: to act as stewards in managing and preserving the environment, and to worship, submit, draw closer to, and know their Creator. In contrast, the Bible describes the responsibility of humanity as exercising dominion over the earth and its contents while maintaining balance. It is hoped that the results of this comparative study will enhance understanding of the similarities and differences between the two scriptures on this theme.